LIG1 is a novel marker for bladder cancer prognosis: evidence based on experimental studies, machine learning and single-cell sequencing - Song, Ding-ming; Shen, Tong; Feng, Kun; He, Yi-bo; Chen, Shi-liang; Zhang, Yang; Luo, Wen-fei; Han, Lu; Tong, Ming; Jin, Yanyang (Frontiers in Immunology, 2024)
### Background Bladder cancer (BLCA) is a highly fatal disease that poses a significant threat to patients. The LIG1 gene, positioned at 19q13.2-13.3 and one of the four DNA ligases in mammalian cells, is frequently deleted in various tumour cells. Despite this, LIG1's precise involvement in BLCA remains unclear. This pioneering investigation explores LIG1's impact on BLCA, aiming to elucidate its interplay with clinicopathological factors. ### Methods We retrieved gene expression data from the GEO repository for para-carcinoma and BLCA tissues. Single-cell sequencing data were processed using the "Seurat" package, and differential expression analysis was performed with the "Limma" package. We constructed scale-free gene co-expression networks using the "WGCNA" package and used a Venn diagram to isolate overlapping genes from the positively correlated modules identified by WGCNA and differentially expressed genes (DEGs). The "STRINGdb" package established the protein-protein interaction (PPI) network. Hub genes were identified through the PPI network using the Betweenness Centrality (BC) algorithm. KEGG and GO enrichment analyses uncovered the regulatory mechanisms and biological functions associated with the hub genes. A machine-learning diagnostic model was established using the "mlr3verse" package. Mutation profiles between the LIG1^high and LIG1^low groups were visualized using the BEST website. Survival analyses within these groups were performed using the BEST and GENT2 websites. Finally, a series of functional experiments validated the role of LIG1 in BLCA. ### Results Our investigation revealed that LIG1 is upregulated in BLCA specimens, with heightened LIG1 levels correlating with unfavorable overall survival outcomes. Functional enrichment analysis of hub genes highlighted LIG1's involvement in DNA replication, cellular senescence, cell cycle, and the p53 signaling pathway. The mutational landscape of BLCA varied significantly between LIG1 high and low groups. Immune infiltrating analyses suggested a pivotal role for LIG1 in immune cell recruitment and regulation within the BLCA microenvironment, impacting prognosis. Subsequent experimental validations further underscored LIG1's significance in BLCA pathogenesis. ### Conclusions Our research demonstrates that LIG1 plays a crucial role in promoting bladder cancer progression by enhancing proliferation, invasion, epithelial-mesenchymal transition (EMT), and other key functions. Thus, LIG1 serves as a potential risk biomarker for bladder cancer.